Testicular Adrenal Rest Tumors: Sonographic and Magnetic Resonance Imaging Characteristics of Its Different Stages - Mohamed Sherif El-Sharkawy (International Journal of Biomedicine)
Testicular adrenal rest tumors (TARTs) are benign lesions that occur in a high percentage of patients with congenital adrenal hyperplasia and are characterized by the deficiency of adrenocortical enzymes, particularly 21-hydroxylase. On imaging, these give different patterns of uncommonly diagnosed focal testicular lesions that can allow differentiation from other focal testicular lesions, particularly germ cell tumors. Progression of the disease reflects characteristic and diagnostic appearance on sonography and magnetic resonance imaging. Awareness of these characteristics in imaging is necessary to avoid unnecessary surgery in the early stages and avoid confusion with other focal testicular lesions, particularly germ cell tumors. This paper reviews serial sonographic and MRI diagnostic features at different stages of TARTs to allow diagnosis and monitor response to treatment.